Anaphylactic and Hemorrhagic Shock during Disseminated Abdominal Hydatidosis Surgery: A Case Report - Kherchttou, Yassine; Driouich, Aicha; Elouardi, Youssef; Khallouki, Mohammed (International Journal of Innovative Research in Medical Science, 2021)
Hydatidosis is a frequent pathology which remains endemic in Morocco. Its preferred location is the liver while the peritoneal location remains rare, even more rarely the pelvic location. The treatment is mainly surgical, but this surgery can be complicated (intraoperatively) by potentially serious accidents, it can be implicated in the occurrence of severe allergic reactions which can be life-threatening, more rarely by hemorrhagic accidents, especially if the cysts keep important and close vascular contact. We report the observation of a case of disseminated peritoneal hydatidosis supra-mesocolic, sub-mesocolic, pelvic and hepatic surgery complicated first by anaphylactic shock and secondarily by hemorrhagic shock. We insist on the need for its rapid recognition in order to quickly institute an adequate and effective treatment. The prevention of this accident is based on surgical precautions to prevent leaks or accidental intraoperative ruptures of hydatid cysts.